Business law : - Twomey, David P. (Thomson/South-Western West, 2004)
BUSINESS LAW: PRINCIPLES FOR TODAY'S COMMERCIAL ENVIRONMENT, also provides the information and resources to assist you in studying for the CPA exam. Based on the #1 business law summarized case text on the market today, this excerpted case version helps you grasp key legal concepts and principles, reinforcing your understanding with applications and examples of real-world dilemmas, issues, and problems. Current, comprehensive, easy-to-understand and fascinating to read, BUSINESS LAW will help you prepare you for every class lecture and gives you all the resources you need to do your best on exams.